"La poesía conversacional costarricense en la construcción de un sociedad solidaria o de equidad desde Elliette Ramírez y Osvaldo Sauma" - Calvo Oviedo, Marlen (2016)
The purpose of this work is approach Costa Rican conversational or colloquial poetry, from a new paradigm that allows us to demonstrate that there does not exist in the poetic writing that occupies to us a sharp division between feminine and masculine, that gender is a biological/social construction that affects both parts and excludes other options, non linear or hierarchic. Our challenge will consist of demonstrating how some men and women, in our case Eliette Ramírez and Osvaldo Sauma, with their poetry break those limitations of gender and open to a speech of equality and solidarity with themselves, allowing: to love, to hate, to perceive, to rationalize and to de-rationalize life and its circumstances.